193 Differences in thyroid immune-related adverse events between lung cancer types, a retrospective analysis. (9th November 2020) - Jiwani, Rahim; Brody, Heather; Mao, Yuxuan; Lee, Elisabeth; Rehana, Rita; Cherry, Cynthia; Bian, Hui; Namireddy, Praveen
Abstract : Background: Immune modulation of the PD-1/PD-L1 pathway is a promising treatment of various malignancies however, alteration of the pathway is known to cause many immune related adverse events (irAEs) including thyroid dysfunction. Whether the frequency of thyroid irAEs differ between lung cancer types has not yet been studied. Methods: A total of three hundred twenty-nine lung cancer patients treated with immunotherapy at East Carolina University between April 2014 and July 2019 were included in a retrospective cohort analysis. Baseline TSH and TSH at each treatment cycle were recorded along with the type of lung cancer, specific agent used, timing of thyroid dysfunction and need for levothyroxine replacement. The frequency of thyroid irAEs as defined by TSH < 0.4 or > 4.0 and its relationship with lung cancer types were analyzed using chi square tests and logistic regression. Results: Of the three hundred twenty-nine patients; 54.4% had adenocarcinoma, 31.6% had squamous cell carcinoma, 11.3% had small cell carcinoma and 2.7% had poorly differentiated lung cancer. Overall, 135 patients (41.0%) developed thyroid irAEs (table 1 ). Pearson's chi square test was used to compare the frequencies of thyroid irAEs for each type of lung cancer against all other lung cancer types. Patients with squamous cell carcinoma developed significantly less thyroid irAEs (32.7%), compared to all other lung cancers (44.9%), X2 (1, N = 329) = 4.4, p = 0.037. Conversely, patients with lung cancer types other than squamous cell carcinoma were more likely to develop thyroid irAEs, OR = 1.68 (95% CI: 1.03 – 2.73). Conclusions: Thyroid irAEs occurred significantly less frequently in patients with squamous cell carcinoma than those with other lung cancer types. This analysis may allow clinicians to better identify patients more likely to develop irAE thyroid dysfunction based on lung cancer type.